2006
DOI: 10.5511/plantbiotechnology.23.191
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Phalaenopsis plants with resistance to Erwinia carotovora produced by introducing wasabi defensin gene using Agrobacterium method

Abstract: Transgenic plants over-expressing wasabi defensin gene were successfully produced in Phalaenopsis orchid by Agrobacterium-mediated transformation method. Embryogenic cell suspension culture of Phalaenopsis Wataboushi '#6.13' was infected with A. tumefaciens strain EHA101 carrying a plasmid containing wasabi defensin gene and selectable marker nptII, hpt genes. Plantlets were regenerated through somatic embryogenesis from the calli selected on hygromycincontaining medium. Transformation of plantlets with wasabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
0
12
0
4
Order By: Relevance
“…In agreement with our results, Lifang et al (2001) demonstrated that the concentrations of the hygromycin used in the regeneration and subculture media for wheat plants was 20 and 30 mg L -1 , respectively. Sjahril et al (2006) reported that 25 mg L -1 hygromycin was used in the regeneration medium for selection of putative transgenic Phalaenopsis orchid plantlets. The results are also consistent with those obtained by Angenon et al (1994) and Cosson et al (2015) as who reported that the selection agent should fully inhibit growth of untransformed plant cells, therefore the lowest concentration of the selection agent that suppresses growth of untransformed cells is generally used.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Lifang et al (2001) demonstrated that the concentrations of the hygromycin used in the regeneration and subculture media for wheat plants was 20 and 30 mg L -1 , respectively. Sjahril et al (2006) reported that 25 mg L -1 hygromycin was used in the regeneration medium for selection of putative transgenic Phalaenopsis orchid plantlets. The results are also consistent with those obtained by Angenon et al (1994) and Cosson et al (2015) as who reported that the selection agent should fully inhibit growth of untransformed plant cells, therefore the lowest concentration of the selection agent that suppresses growth of untransformed cells is generally used.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of WD was found to inhibit the growth of the rice blast fungus in vitro (Saito et al 2001). Earlier studies on the expression of WD in transgenic Nicotiana benthamiana (Saito et al 2001;Kiba et al 2003), rice (Kanzaki et al 2002), potato (Khan et al 2006b), Phalaenopsis (Sjahril et al 2006), and ''Egusi'' melon (Colocynthis citrullus) (Ntui et al 2010) all showed the enhanced antimicrobial activities of this protein.…”
Section: Molecular Analysesmentioning
confidence: 93%
“…In an earlier study, we produced transgenic potato plants carrying wasabi defensin that exhibited antifungal activity against B. cinerea (Khan et al 2006b). Transgenic Phalaenopsis plants expressing wasabi defensin protein (WD) showing resistance to Erwinia caratovora have also been produced (Sjahril et al 2006). Transgenic 'Egusi' melon (Colocynthis citrullus) was produced recently that exhibited resistance against Aletnaria leaf spot and Fusarium wilt (Ntui et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Numerous varieties of Phalaenopsis have been developed and registered with the Royal Horticulture Society (RHS) each year. However, very limited research efforts have been devoted to understanding the genetic diversity (Been et al, 2002;Chang et al, 2009) or the genomic features of Phalaenopsis (Hsu et al, 2008) and genetic transformation (Liao et al, 2004;Sjahril et al, 2006). Although one Phalaenopsis genome was recently sequenced (Cai et al, 2015), the inheritance of important ornamental or horticultural traits, genetic relationships among important species, and the genomic organization of Phalaenopsis remained poorly understood, due to the complex genetic background and extensive hybridization in this genus.…”
Section: Introductionmentioning
confidence: 99%